Voltaire's Tancrède - Henderson, J (Voltaire Foundation, 2017)
Preface Introduction Chapter I. Events preceding publication Chapter II. The first edition Chapter III. The revised Prault edition Chapter IV. The first Cramer edition Chapter V. Conclusion Appendices I. Textual modifications made by Prault in the third corrected state of signature F, F-3, of his 1760/1761 first edition. II. Textual modifications made by Prault in cancels Av-1, Biij-1, Biij-2, Bvij-1, and Bvij-2 inserted in copies of his 1760/1761 first edition. III. Unplanned textual deviations in signatures C, D, and E of the 1760/1761 Prault first edition IV. The 1760/1761 Prault first edition: copies with 1760 titlepages. V. The 1760/1761 Prault first edition: copies with 1761 titlepages. VI. The 1761 Prault revised edition VII. The 1761 Cramer edition VIII. Photocopies of (A) the 1760 Prault titlepage, (B-C) the 1761 Prault titlepages (cancels Aij-1 and Aij-2), (D) the 1761 Cramer half-title, (E) leaf [Aviij], recto, of the 1760/1761 Prault first edition, and (F) leaf A2, recto, of the 1761 Cramer edition. IX. The annotated British Museum text (facsimile)